(untitled) (Nexo Revista Científica, 2023)
The presence of high levels of ammonia in the bloodstream can lead to unconsciousness and convulsions, making it a prime example of dangerous air pollution. The presence of certain gases in our environment can be quite discomforting. In light of these concerns, we present a contemporary approach to designing and developing an exceptionally sensitive ammonia gas sensor. This sensor utilizes a substrate composed of single-mode fiber (SMF), photonic crystal fiber (PCF), and SMF to create a Mach-Zehnder interferometer (MZI). The sensing mechanism involves the immobilization of an Au and GO nanocomposite. In this setup, the region of interference between the waves of the SMF and the solid crystal fiber creates a collapse zone that is utilized to excite the core and cladding modes of the PCF. This innovative technique ensures remarkably rapid response and recovery times.The reusable probe showcased in this study displays significant potential for achieving rapid, highly accurate, and reproducible ultratrace ammonia detection. This introduces a novel avenue for conducting online measurements and environmental monitoring. The intersection point of the SMF and the solid crystal specialty fiber generates a collapse zone that effectively excites the core and cladding modes of the PCF, resulting in the promised rapid response and recovery times.The reusable probe exhibits the capability to swiftly detect ultratrace amounts of ammonia, boasting good selectivity, consistent characteristics, and sensitivities of up to 18.65 nm/ppm. This development opens up new possibilities for environmental monitoring and real-time measurements, offering improved insights into our surroundings.